IMPROVING THE METHODOLOGY OF DEVELOPING LITERARY AND SPEECH COMPETENCE IN 8TH GRADE STUDENTS - Meylikulova Manzura Abdullayevna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The scientific-theoretical justification of the development of the structural components of students' speech competence, the development of oral and written speech, the independent expression of one's opinion, the development of a creative approach to creating a text, and the acquisition of speech culture is one of the most important and relevant topics today. It is on the topic of improving the methodology of developing literary and speech competence in 8th grade students.